Evaluating the Impact of Differentiated Instruction on English Language Proficiency in EFL Classrooms: A Meta-Analytic Perspective - Mujiono, Mujiono; Fatimah, Siti (Jurnal Pendidikan Progresif, 2025)
Evaluating the Impact of Differentiated Instruction on English Language Proficiency in EFL Classrooms: A Meta-Analytic Perspective. Objectives: The study analyzes the impact of Differentiated Instruction (DI) practice on enhancing English proficiency among EFL learners on various levels, concerning particular skills, objectives, and educational settings․ Methods: The meta-analysis followed the PRISMA guidelines and synthesized seven quantitative studies from 2020 to 2024, which applied DI in the EFL classroom and examined writing, speaking, reading, or general proficiency results. Random-effects models were calculated based on the pooled effect size, and moderator analyses were run by looking at skill type and learner educational level as moderators for the effect size․ Findings: The practice of DI has been reported to have a favorable and context-dependent impact on English proficiency, with a Standardized Mean Difference (SMD) of 1.41 [95% CI: 0.48, 2.34]; however, the presence of considerable variability (I² = 95%) in the results calls for careful interpretation. According to the subgroup analysis, the DI effects are more pronounced on productive skills, specifically speaking (SMD = 2.50) and writing (SMD = 1.68), than on general English proficiency (SMD = –0.05). In total, DI is a powerful method to facilitate EFL learning, provided that it is implemented with recognition of the context and appropriate pedagogical strategies. Conclusion: DI presents a sturdy, learner-centred approach to EFL teaching․ Therefore, programs developed for DI implementation should give teachers enough liberty of contextualization; teachers should undergo adequate training, and programs should be guaranteed institutional commitment․ DI can be strategically implemented by means of scaffolded tasks, flexible grouping, multimodal resources, and digital platforms to enhance the levels of engagement and achievement․ Future research should consider the long-term effects, expand evidence in different contexts, and adapt DI for the needs of higher education learners with modern technology in mind and a more collaborative approach․ Keywords: differentiated instruction, EFL, English proficiency,  learner-centered pedagogy.